Perceived risk for falls and decision-making in riding raised ramps in mountain biking: a pilot study - Chilton, Emily P.; Robinovitch, Stephen N. (Frontiers in Psychology, 2023)
Mountain biking (MTB) is a challenging activity where riders face constant decisions on whether to attempt technical paths or features (e.g., wooden ramps and jumps) that pose risk for falls and injuries. Risk homeostasis theory posits that riders pursue an optimal non-zero level of risk that balances the rewards of attempting challenging features with the need to avoid unreasonable risk for injury. Little is known on how riders judge risk, and the level of risk that riders deem unacceptable. We conducted experiments with experienced MTB riders (n=17) to examine how their willingness to ride raised wooden ramps depended on their perceived probability for falling (Pf) and their perceived probability for injury in the event of a fall (Pi) while riding the ramp. In one experiment, participants viewed ramps of varying widths and heights and described their willingness to ride each ramp, along with Pf and Pi. We found that Pf and Pi were independent predictors of willingness to attempt ramps. Moreover, the product Pf*Pi (the perceived risk for injury in attempting the ramp) was a stronger predictor than Pf or Pi alone. In a second experiment, participants viewed ramps of different widths, and reported the maximum (threshold) height where they would ride each ramp, along with Pf and Pi. We found that Pf*Pi at the threshold height, averaging 13%, did not vary with ramp width. We conclude that decisions on riding ramps are based on the product Pf*Pi. On average, riders refused to ride ramps when Pf*Pi exceeded 13%.